2018
DOI: 10.1523/eneuro.0422-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

PICK1-Deficient Mice Exhibit Impaired Response to Cocaine and Dysregulated Dopamine Homeostasis

Abstract: Protein interacting with C-kinase 1 (PICK1) is a widely expressed scaffold protein known to interact via its PSD-95/discs-large/ZO-1 (PDZ)-domain with several membrane proteins including the dopamine (DA) transporter (DAT), the primary target for cocaine’s reinforcing actions. Here, we establish the importance of PICK1 for behavioral effects observed after both acute and repeated administration of cocaine. In PICK1 knock-out (KO) mice, the acute locomotor response to a single injection of cocaine was markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…[146,147] It is highly evolutionarily conserved from invertebrates to humans, which suggests that PICK1 has important biological functions. [158][159][160] The BAR domain of PICK1 is a domain that facilitates dimerization of PICK1. [158][159][160] The BAR domain of PICK1 is a domain that facilitates dimerization of PICK1.…”
Section: Targeting the Pdz Domain Of Protein Interacting With C Kinasementioning
confidence: 99%
See 3 more Smart Citations
“…[146,147] It is highly evolutionarily conserved from invertebrates to humans, which suggests that PICK1 has important biological functions. [158][159][160] The BAR domain of PICK1 is a domain that facilitates dimerization of PICK1. [158][159][160] The BAR domain of PICK1 is a domain that facilitates dimerization of PICK1.…”
Section: Targeting the Pdz Domain Of Protein Interacting With C Kinasementioning
confidence: 99%
“…[173] Both peptides could efficiently displace the interaction between PICK1 and GluA2 in COS7 cells, but while Pep2-SVKI was found to inhibit LTD, Pep2-EVKI did not show an effect on LTD. [158,176] To elucidate the importance of the interaction between PICK1 and DAT, the 24 C-terminal residues of DAT, which contains both a PICK1 binding site at the extreme C-terminal and a Ca 2+ /calmodulin-dependent protein kinase IIα (CamKIIα) binding site upstream of the PICK1 binding site, was fused to the Tat CPP motif to render the peptide cell permeable (Tat-DATC24). [173] Later studies have shown that Pep2-EVKI could reduce the reinstatement of cocaine seeking through decoupling of the AMPAR C-terminal/PICK1-PDZ interaction after intra-accumbal shell administration.…”
Section: Targeting the Pdz Domain Of Protein Interacting With C Kinasementioning
confidence: 99%
See 2 more Smart Citations
“…1517,19,20 Furthermore, the disruption of PICK1-DAT interactions impairs the behavioral effects of cocaine in mice. 21 With this, PICK1 has been identified as an integral player in drug addiction. 22 Consequently, efforts have been made to identify small molecules with the potential to inhibit the function of PICK1.…”
Section: Introductionmentioning
confidence: 99%